2014
DOI: 10.1371/journal.pone.0111775
|View full text |Cite
|
Sign up to set email alerts
|

Energy Balance Related Behaviour: Personal, Home- and Friend-Related Factors among Schoolchildren in Europe Studied in the ENERGY-Project

Abstract: ObjectiveTo design interventions that target energy balance-related behaviours, knowledge of primary schoolchildren's perceptions regarding soft drink intake, fruit juice intake, breakfast consumption, TV viewing and physical activity (PA) is essential. The current study describes personal beliefs and attitudes, home- and friend-related variables regarding these behaviours across Europe.DesignCross-sectional study in which personal, family and friend -related variables were assessed by validated questionnaires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 53 publications
0
31
0
4
Order By: Relevance
“…Story et al 16 , observed in their study that overweight subjects had strong intentions of choosing a healthier diet; the same was reported by Sabiston & Crocker 24 , possibly because normal weight schoolchildren have no need to change their dietary behaviour to achieve changes in their bodies 13 . Iannotti & Wang 25 say that young whites present many obesogenic behaviours, with excess weight of up to 29.7%.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…Story et al 16 , observed in their study that overweight subjects had strong intentions of choosing a healthier diet; the same was reported by Sabiston & Crocker 24 , possibly because normal weight schoolchildren have no need to change their dietary behaviour to achieve changes in their bodies 13 . Iannotti & Wang 25 say that young whites present many obesogenic behaviours, with excess weight of up to 29.7%.…”
Section: Discussionmentioning
confidence: 55%
“…Overweight and obese children live in more obesogenic and sedentary environments, closer to fast-food outlets and other sources of very dense, high-energy foods, and where outdoor physical activity is not encouraged due to the availability of indoor entertainment and vehicle travel 14 . Eating a proper breakfast and/or not skipping breakfast, together with higher consumption of dairy products, were related with a healthier diet and lower BMI; consumption of fibre-rich foods (fruit, vegetables and whole-grain products) was related with lower thickness of cutaneous folds 13,18 ; this was corroborated by Vilchis-Gil et al 27 , who found that higher intake of fruit is associated with lower BMI. Furthermore, higher consumption of carbohydrates (traditional foods with added fat), soft drinks and natural fruit juice were associated with a risk of greater obesity 27 .…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Dari berbagai negara di Eropa, anak-anak dari Hungaria memiliki sikap dan perilaku konsumsi soft drink yang lebih tinggi dari negara lainnya karena sikap dan perilaku orang tua dan teman sebaya yang mendukung konsumsi soft drink. 20 Uang saku seorang anak dapat mencerminkan tingkat sosial ekonomi keluarga. Seorang anak yang berasal dari keluarga dengan status pekerjaan orang tua yang rendah memiliki kecenderungan untuk mengkonsumsi soft drink lebih banyak 8 .…”
Section: Metodeunclassified